Floating rafts as breeding habitats for the Common tern, Sterna hirundo. Colonization patterns, abundance and reproductive success in Venice Lagoon - Francesca Coccon; Stefano Borella; Nicola Simeoni; Stefano Malavasi (Rivista Italiana di Ornitologia, 2018)
The Venice lagoon hosts the 15% of the entire Italian breeding population of Common terns, Sterna hirundo, highlighting the great value of the area for this species. However, in the last 25 years, a substantial decline of Common terns has been detected in the Lagoon, which culminated in 2008. The main causes of this negative trend were the loss of salt marsh habitats, where terns typically breed in the Venice lagoon. This was due to the increase in the mean sea level and the greater frequency of high tides during the reproductive period with consequent flooding of their breeding sites; competition with yellowlegged gulls (Larus michahellis), predation and human disturbance. As a preliminary experimental approach to counter the depletion of the species and favour its recovery, we performed a habitat loss compensation project by setting up four floating rafts (3x2m), covered by two different types of substrate (sandy and vegetal substrate). This was to function as an artificial nesting site safe from flooding, positioned in a protected internal wetland area of the Venice lagoon, Valle Averto (Sourthern Lagoon). We studied the colonization patterns of the rafts and the reproductive success of Common tern breeding pairs during the 2014 and 2015 breeding seasons. We also investigated those environmental and structural variables that could favour the use of the rafts and the nesting success of the species. In both years, the rafts were successfully colonized and used by terns for nesting. Our results also indicated higher temperature, lower rainfall and greater distance from the shore as the main habitat factors favouring the occurrence and the reproductive success of the breeding pairs, while a windrow of dead plants was indicated as the preferred substrate for covering rafts in order to make them more attractive. The results provided some suggestions for successful restoration plans to be developed in similar lagoon areas.